Self-assembled M(12)L(24) nanospheres as a reaction vessel to facilitate a dinuclear Cu(i) catalyzed cyclization reaction - Gonell, Sergio (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
The application of large M(12)L(24) nanospheres allows the pre-concentration of catalysts to reach high local concentrations, facilitating reactions that proceed through dinuclear mechanisms. The mechanism of the copper(i)-catalyzed cyclization of 4-pentynoic acid has been elucidated by means of a detailed mechanistic study. The kinetics of the reaction show a higher order in copper, indicating the formation of a bis-Cu intermediate as the key rate determining step of the reaction. This intermediate was further identified during catalysis by CIS-HRMS analysis of the reaction mixture. Based on the mechanistic findings, an M(12)L(24) nanosphere was applied that can bind up to 12 copper catalysts by hydrogen bonding. This pre-organization of copper catalysts in the nanosphere results in a high local concentration of copper leading to higher reaction rates and turnover numbers as the dinuclear pathway is favored.